In situ transmission electron microscopy observation of electrochemical process between Li-C nanocomposites and multilayer graphene - Lin, Wei Ming; Suresh, Giri; Gupta, Vikaskumar Pradeepkumar; Tomida, Shota; Oyama, Kento; Yaakob, Yazid; Asaka, Toru; Sonoyama, Noriyuki; Mohd Yusop, Mohd Zamri; Tanemura, Masaki (Wiley, 2024)
Portable power supplies, particularly lithium‐ion batteries (LIBs), will play a key role in achieving sustainable development goals, and electrode active materials for the next generation of LIBs with higher energy density and longer life time is highly demanded. For this, in situ visualization of Li behavior during the charge/discharge process is essential, and transmission electron microscopy (TEM) will be promising for this purpose. Here, a quite simple experimental setup consisting of a newly developed Li–C nanocomposite film sputter‐deposited onto Au nanoprotrusions at room temperature and graphene synthesized on a W probe at 500 °C for the in situ TEM observation of the battery reaction is proposed. The preservation of the metallic Li in the Li–C film that is transferred to TEM without using any transfer vessels under atmospheric conditions is confirmed by high resolution TEM before the in situ electrochemical process in TEM. After the one cycle of the in situ electrochemical process, the intercalation of Li ions into graphene (lithiation) is clearly observed. Thus, it is concluded that the metallic Li stored in the Li–C film works well as the anode active material in the electrochemical process for solid state LIBs, implying the developed in situ experimental system is promising.